Age-related differences in motives for contacting out-of-hours primary care: a cross-sectional questionnaire study in Denmark - Grete Moth; Morten B. Christensen; Helle Collatz Christensen; Anders H. Carlsen; Ingunn S. Riddervold; Linda Huibers (Taylor & Francis Group, 2020)
Objective Demands for out-of-hours primary care (OOH-PC) services are increasing. Many citizens call because of non-urgent health problems. Nevertheless, the patients' motives for requesting medical help outside office hours remains an understudied area. This study aimed to examine motives for calling OOH-PC services in various age groups. Design Cross-sectional paper based questionnaire study conducted during two weeks in 2015. Setting The OOH-PC services in two Danish regions. Subjects Randomly selected patients calling the two healthcare services and accepting to participate in the study received a questionnaire on patient characteristics, health problems, and 26 pre-defined motives based on the Andersen Behavioural Model. Multivariate regression analyses were conducted for various age groups to calculate the probability of each motive to be a significant factor for the decision to call. Results A total of 1,871 patients were included in the study; half were parents of children aged 0-12 years. Young adults (18 to 39 years) differed significantly from other age groups as they more often stated perceived barriers and benefits such as "Own GP no time available soon enough" and "Need for quick help because of work". Conclusion Young adults more often perceive barriers and benefits, which may suggest af difference in expectations regarding the purpose of out-of-hours services and accessibility. Further research is needed to address this issue and further explore the potential gap between the citizens' expectations to the OOH-PC services and the prevailing health policies.Key points The out-of-hours primary healthcare services are increasingly contacted for non-urgent problems, but little is known about the citizens' motives for calling. Age is associated with differences in the perceived importance of various motives for calling out-of-hours care. Young adults are more often than other age groups motivated to call due to logistical issues, such as their job.